DIROFILARIASIS OF THE PENIS - O. S. Streltsova; V. N. Krupin; E. V. Grebenkin; M. V. Mamonov; A. A. Osipov (Вестник урологии)
This article presented a rare clinical case in Urology - Dirofilariasis of the penis. Filaria are biohelminths, which are most common in tropical countries. Dirofilariasis is the only human filariasis, found in the territory of the Russian Federation. Mosquitoes are carriers of the disease. Changing climate conditions in the direction of warming, the availability of international travel, non-compliance with preventive measures lead to an increase in the number of cases of infection by helminths, including rare species.